Marine Sponge Petrosia sp. from Maratua Island: A Potential Source of Antibiofilm Agents Against Pathogenic Biofilms - Mochtar, Chaerul Fadly; Hamzah, Hasyrul; Bakti, Muhammad Tursina; Rozak, Abdul (Journal of Basic Medical Veterinary, 2025)
Microbial biofilm-associated infections, particularly those caused by Pseudomonas aeruginosa and Candida albicans, have emerged as global challenges due to resistance to conventional antimicrobials. This study investigated the antibiofilm activity of ethanol extract from the sponge Petrosia sp., collected from the waters of Maratua Island, against both pathogens. Extraction was performed using 96% ethanol maceration, followed by in vitro biofilm inhibition and eradication assays using the broth microdilution method in microtiter plates. Biofilm density was quantified through crystal violet staining and absorbance measurement (OD₅₉₅ nm). The results demonstrated that the extract inhibited both intermediate-stage (24 hours) and mature-stage (48 hours) biofilm formation, with an MBIC₅₀ of 0.125% for both microorganisms. At a concentration of 1%, the inhibition percentages reached 73.86% for P. aeruginosa and 84.70% for C. albicans. The highest mature biofilm eradication activity was observed at 1% concentration, with MBEC₅₀ values of 51.98% for P. aeruginosa and 80.53% for C. albicans, approaching the effectiveness of positive controls (nystatin 82.04% and chloramphenicol 61.72%). The extract exhibited a dose-dependent pattern, with greater efficacy against C. albicans, possibly due to differences in biofilm matrix composition. These findings confirm the potential of Petrosia sp. as a source of multitarget antibiofilm compounds, particularly for fungal infections, and underscore the significance of Indonesia’s marine biodiversity as a basis for innovative therapeutic development.